2017
DOI: 10.20944/preprints201709.0100.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cut-off Values of Hematologic Parameters to Predict the Number of Alpha Genes Deleted in Subjects with Deletional Alpha Thalassemia

Abstract: Most of α-thalassemia cases are caused by deletions of the structural α-globin genes. The 12 degree of microcytosis and hypochromia has been correlated with the number of affected α-globin 13 genes, suggesting a promising role of hematologic parameters as predictive diagnostic tools.14 However, cut-off points for these parameters to discriminate between the different subtypes of α- 25

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…However, in our experience, we have observed that MCV values are usually less in alpha‐thalassemia 1 trait than that in beta‐thalassemia trait and the two entities may need different optimal cutoffs. Our observation is supported by the finding reported by Velasco‐Rodríguez et al who found that the best cutoff of MCV for alpha‐thalassemia 1 trait was ≤70.80 fL. However, the number of the cases in their study was relatively small.…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, in our experience, we have observed that MCV values are usually less in alpha‐thalassemia 1 trait than that in beta‐thalassemia trait and the two entities may need different optimal cutoffs. Our observation is supported by the finding reported by Velasco‐Rodríguez et al who found that the best cutoff of MCV for alpha‐thalassemia 1 trait was ≤70.80 fL. However, the number of the cases in their study was relatively small.…”
Section: Introductionsupporting
confidence: 91%
“…Velasco‐Rodríguez et al tried to differentiate different subtypes of alpha‐thalassemia. They found that mean MCV for alpha‐thalassemia 1 trait were 67.34 ± 3.88 fL and suggested MCV ≤70.80 fL to be the cutoff value for alpha‐thalassemia 1 trait which provided a sensitivity and a specificity of 85.9% and 86.25%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Another interesting finding was the tendency of red cell volume distribution width (RDW) elevation proportionally to the loss of the alpha genes, corroborating with other studies in the literature. e thalassemia patients have smaller and more homogeneous erythrocytes (mainly microcytic), which leads us to correlate high RDW in iron deficiency than in thalassemia [34][35][36].…”
Section: Resultsmentioning
confidence: 99%
“…The same results suggest iron deficiency anemia, which was likely to indicate thalassemia in ethnic populated regions of countries at risk (20). In the literature, specifically, MCH, MCV, and RDW parameters were used in the differentiation of HMPs (21)(22)(23)(24). In our study, MCV, MCH, and RDW were significantly different in the groups with HMP in both genders than the control group.…”
Section: Discussionmentioning
confidence: 94%